Tensile Behavior of Alternative Reinforcing Materials as Fiber Reinforced Cementitious Mortar FRCM - A. Mousa, Mohammed (International Journal of Engineering and Technology, 2018)
The adoption of new reinforcing and retrofitting materials provide an alternative and affordable techniques that can be utilized in low-income communities. FRCM is comprised of a broad spectrum family of reinforcing materials such that it allowed utilizing affordable local alternatives such as fishing net FN and welded wire steel mesh WWSM. The composite effectiveness stems from the compatible inorganic matrix properties which have similar properties to the substrate unlike other composites such as FRP. The tensile response of FN and WWSM and their mortar composites has been experimentally studied to characterize their strength, deformation, and the bonding between the reinforcement and the mortar. Experimental investigations on dog-bone composites specimens with their materials samples subjected to uniaxial tensile load were performed. The experimental campaign included testing 12 composite specimens taking into account multiple parameters like material, thread thickness, and the layer effect. The results show comparable strengths and high deformation capacity (12.5 times) of FN to the WWSM. Finally, the SEM imaging shows a well-impregnation between the mortar and the reinforcement of both materials. The tensile response of the composite emphasizes its potential as structural retrofitting and hazard mitigation technique for local builders and house owners in developing countries.